Surgical trainees benefit from good consultant working practices: an audit on the effect on training of a new consultant rota. Issue 970 (4th August 2006) - Majed, A R I; Riaz, A A; Das-Purkayastha, P; Martin, W; Gregg-Smith, S J
Abstract : Purpose: To retrospectively assess operative supervision for orthopaedic trainees over an 18 week period when trauma and orthopaedic consultants changed their on call working practice from one week on call to a four day/three day block, during a fortnight period. Outcome: The rota changes had important implications on workload and consultant availability to supervise juniors during operation with a positive effect upon training such that trauma surgery supervision rates increased significantly (p<0.001) after the introduction of these new working arrangements. Working life for consultants and ultimately patient care were also felt to improve and consultants' working hours were closer to the European working hours directives.